2022
DOI: 10.1002/solr.202200620
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Photoconversion from In‐Plane 2D Heterostructures of 2D Transition Metal Carbides/Semiconductors

Abstract: 2D transition metal carbides/nitrides (MXenes) are thought of promising photothermal materials due to their broadband localized surface plasma resonance (LSPR) and attractive electromagnetic interference (EMI) properties. However, the weak oxidation resistance and unclear photothermal mechanism of MXenes impede their photothermal modulations. Herein, the in‐plane 2D Ti3C2/TiO2 heterostructures are fabricated by partial oxidation and an unconventional photothermal effect under near infrared irradiation, even if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The fact that strain alone is not sufficient to activate the inert base of TMDs is also highlighted. The emerging transition metal carbon/nitrides (MXenes) with tunable band gap properties and excellent mechanical strength are candidates for HER catalysts, 98,99 but few studies were reported so far. The O* surface functional groups of MXenes are the active sites of HER and the strong interaction between H atoms and O* limits the HER activity.…”
Section: D Materialsmentioning
confidence: 99%
“…The fact that strain alone is not sufficient to activate the inert base of TMDs is also highlighted. The emerging transition metal carbon/nitrides (MXenes) with tunable band gap properties and excellent mechanical strength are candidates for HER catalysts, 98,99 but few studies were reported so far. The O* surface functional groups of MXenes are the active sites of HER and the strong interaction between H atoms and O* limits the HER activity.…”
Section: D Materialsmentioning
confidence: 99%
“…The hot electrons are formed from the excitation of the occupied state to the unoccupied state and then converted into heat energy. 112,113 However, Zhang et al 114 pointed out that the weak oxidation resistance and unclear photothermal mechanism of MXenes hindered their photothermal modulation. They fabricated in-plane two-dimensional Ti 3 C 2 /TiO 2 heterostructures by partial oxidation, and demonstrated an unconventional photothermal effect under NIR irradiation, that is, oxidation damaged the LSPR capability.…”
Section: Optical Properties and Photothermal Conversion Of Mxenesmentioning
confidence: 99%
“…Figure a illustrates a schematic diagram showing the formation of vacancy defects on Ti 3 C 2 and the subsequent insertion of Pt atoms. Briefly, the 2D Ti 3 C 2 nanosheets were fabricated by our previously reported methods. , During this procedure, some oxygen-containing termination groups were attached to the surface of Ti 3 C 2 , including −OH and −O groups. After that, a low-temperature hydrothermal treatment was utilized to create vacancies for immobilizing the Pt atoms.…”
mentioning
confidence: 99%